Storytelling in Interactive 3D Geographic Visualization Systems - Thöny, Matthias; Schnürer, Raimund; Sieber, René; Hurni, Lorenz; Pajarola, Renato (ISPRS international journal of geo-information, 2018)
The objective of interactive geographic maps is to provide geographic information to a large audience in a captivating and intuitive way. Storytelling helps to create exciting experiences and to explain complex or otherwise hidden relationships of geospatial data. Furthermore, interactive 3D applications offer a wide range of attractive elements for advanced visual story creation and offer the possibility to convey the same story in many different ways. In this paper, we discuss and analyze storytelling techniques in 3D geographic visualizations so that authors and developers working with geospatial data can use these techniques to conceptualize their visualization and interaction design. Finally, we outline two examples which apply the given concepts.